2021
DOI: 10.18388/abp.2020_5386
|View full text |Cite
|
Sign up to set email alerts
|

Black rice cultivar from Java Island of Indonesia revealed genomic, proteomic, and anthocyanin nutritional value

Abstract: Black rice is considered to be functional food containing anthocyanins as bioactive compounds. This study examined the genomic and proteomic patterns in local black rice from Java Island, Indonesia, with attention to the mechanism of anthocyanin synthesis. Three kinds of black rice from Java Island, including black rice from East Java (BREJ), black rice from Central Java (BRCJ), and black rice from West Java (BRWJ), were studied in comparison to white rice (WREJ) and red rice (RREJ). Genomic profiling was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
0
0
2
Order By: Relevance
“…Phytosterol was reported that inhibit cholesterol absorption [14,15,[17][18][19][20]. Anthocyanins from black rice also ameliorated hyperlipidemia based on in vivo and silico studies [21][22][23][24]. Previous research reported that an isoflavone from lactic-acid fermented soy milk lowered lipid gene metabolism expression in rats fed a high cholesterol diet [17].…”
Section: Discussionmentioning
confidence: 99%
“…Phytosterol was reported that inhibit cholesterol absorption [14,15,[17][18][19][20]. Anthocyanins from black rice also ameliorated hyperlipidemia based on in vivo and silico studies [21][22][23][24]. Previous research reported that an isoflavone from lactic-acid fermented soy milk lowered lipid gene metabolism expression in rats fed a high cholesterol diet [17].…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa bahan herbal yang dilaporkan memiliki aktivitas antidiabetes antara lain kopi (Bare et al, 2019b), beras hitam (Fatchiyah et al, 2020(Fatchiyah et al, , 2023Sari et al, 2021), beras merah (Agustin et al, 2021), Morus alba L., Trigonella foenum-graecum L., Cinnamomum zeylanicum J.Presl, Panax ginseng C.A.Meyer, Phaseolus vulgaris L. (Przeor, 2022), Zingiber officinale Rosc. , Cinnamomum burmannii (Bare et al, 2019a), Senna alexandrina (Rosmalena et al, 2022), Caesalpinia sappan (Sari et al, 2022a), Ruellia tuberosa (Safitri et al, 2020), Momordica charantia (Patel et al, 2012), Allium sativum (Patel et al, 2012), dan lainnya.…”
Section: Pendahuluanunclassified
“…Mekanisme antidiabetes pada herbal diantaranya menghambat alpha amylase, alpha glukosidase, memperbaiki kerusakan pankreas, liver dan ginjal (Roosdiana et al, 2020;Safitri et al, 2021b). Selain itu, beberapa senyawa yang terkandung dalam herbal juga menurunkan efek diabetes mellitus dengan meningkatkan aktivitas antioksidan (Sari et al, 2021;Fatchiyah et al, 2023), mencegah dan memperbaiki disfungsi sel beta pankreas, berperan sebagai agen terapi komplikasi diabetes mellitus (Przeor, 2022), dan efek hipolipidemia (Sari et al, 2020(Sari et al, , 2023c(Sari et al, , 2023b.…”
Section: Pendahuluanunclassified